Ragam Bahasa Jenaka dalam Grup WhatsApp Mahasiswa - Yuliati, Wiwik; Aprilia, Amanda; Maharani, Dewi; Ramadhani, Dina Olivia Zahrah (Kajian Bahasa dan Sastra (KABASTRA), 2025)
The development of online communication technology today has changed student interaction patterns, including academic communication through class WhatsApp groups. Class WhatsApp groups have become a medium for conveying lecture information, and humorous language often appears within these groups as part of student social interactions. This study aims to describe the forms and types of humorous language used by students and to understand their function in the context of academic communication. This study uses a descriptive qualitative approach with data sources in the form of conversations between students in a WhatsApp group on November 25, 2025. Data collection was carried out through observation and documentation methods, while data analysis used context analysis. The results show that the humorous language that emerged in this WhatsApp group conversation is classified into three types: social humor, political humor, and religious humor. These humors aim to lighten the atmosphere, strengthen relationships between students, and create a more relaxed interaction space without eliminating the group's main function as a medium for academic communication.